2015
DOI: 10.1093/jjfinec/nbv003
|View full text |Cite
|
Sign up to set email alerts
|

Term Structure Persistence

Abstract: Stationary I(0) models employed in yield curve analysis typically imply an unrealistically low degree of volatility in long-run short-rate expectations due to fast mean reversion. In this paper we propose a novel multivariate affine term structure model with a two-fold source of persistence in the yield curve: Long-memory and short-memory. Our model, based on an I(d) specification, nests the I(0) and I(1) models as special cases and the I(0) model is decisively rejected by the data. Our model estimates imply b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 64 publications
3
40
0
Order By: Relevance
“…evidence that rational agents require nominal rates to adjust in response to movements in "tax-adjusted" expected inflation. Crowder and Hoffman (1996) showed that the choice of estimator is crucial, an issue further investigated by Caporale and Pittis (2004) Barkoulas and Baum (1997), Meade and Maier (2003), Gil-Alana (2004a,b), Couchman, Gounder and Su (2006), Gil-Alana and Moreno, 2012, Haug, 2014, Apergis et al, 2015, Abbritti et al (2016, etc. As for inflation rates, evidence of long memory has been reported in many papers including Hassler (1993), Delgado and Robinson (1994), Hassler and Wolters (1995), Baillie et al (1996), Baum et al (1999), Hyung et al (2006, Kumar andOkimoto (2007), etc.…”
Section: The Fisher Effect: a Brief Literature Reviewmentioning
confidence: 99%
“…evidence that rational agents require nominal rates to adjust in response to movements in "tax-adjusted" expected inflation. Crowder and Hoffman (1996) showed that the choice of estimator is crucial, an issue further investigated by Caporale and Pittis (2004) Barkoulas and Baum (1997), Meade and Maier (2003), Gil-Alana (2004a,b), Couchman, Gounder and Su (2006), Gil-Alana and Moreno, 2012, Haug, 2014, Apergis et al, 2015, Abbritti et al (2016, etc. As for inflation rates, evidence of long memory has been reported in many papers including Hassler (1993), Delgado and Robinson (1994), Hassler and Wolters (1995), Baillie et al (1996), Baum et al (1999), Hyung et al (2006, Kumar andOkimoto (2007), etc.…”
Section: The Fisher Effect: a Brief Literature Reviewmentioning
confidence: 99%
“…where yt is the time series we observe and zt is a (kx1) vector of deterministic terms that might include a constant and a time trend. This test has a standard null limit distribution and its functional form can be found in any of the numerous empirical applications of the tests, (see, e.g., Gil-Alana and Robinson, 1997;Moreno, 2012 andAbbritti et al, 2016 among others). Additionally, we use a semiparametric approach (Robinson, 1995) that is also based on the Whittle function and that uses only a band of frequencies degenerating to zero.…”
Section: Long-memory Approachmentioning
confidence: 99%
“…However, the available empirical evidence is quite mixed. Mandelbrot [2], Greene and Fielitz [3], Booth et al [4], Helms et al [5], Mynhardt et al [6], Abbritti et al [7], Urquhart [8], Nystrup et al [9], Bariviera [10], Niu and Wang [11], Caporale et al [12], Phillip et al [13] all provided evidence of long memory behaviour in financial markets. By contrast, Lo [14], Jacobsen [15], Berg and Lyhagen [16], Crato and Ray [17], Batten et al [18] and Serletis and Rosenberg [19], Lu and Perron [20] did not find long-memory properties in financial series.…”
Section: Introductionmentioning
confidence: 99%